When is it an African NREN: Building a Vibrant and Sustainable National Research and Education Network in Africa - Eshun, Benjamin A. (My University, 2016)
A National Research and Education Network (NREN) is both; 1) a high performance communications network owned and operated for and by the education and research community of a country and; 2) the organization that operates that network, constituted as a consortium of members, a dedicated agency, a company, NGO, or other type of body. In World Bank partner countries an NREN may simply be a consortium of universities that organize themselves as a “buying club” in order to get a better price from Internet Service providers (ISPs), or it may be more sophisticated and be offering connectivity services to its members. (Case for NRENs 2009). Several countries around the world have adopted the NREN as the centerpiece of an advanced network for collaboration and communication between the Tertiary and Research Institutions within their country and to other parts of the world. (Ravinder 2008; C@ribNET 2010). Around the time of GARNET’s inception in 1995, the United States Congress took critical steps toward what was called then the National Public Network. The United States Senate and the House of Representatives moved toward enacting legislation to authorize their NREN (Kahn 1992). Yet in the context of Ghana and most other Africa Countries, the lacking of similar political strong intervention is what could have led to slow deployment of the NREN. Poor Internet connectivity is one of the pertinent issues in the digital divide between developing and industrialized countries, hampering the transition to the global information society. Africa is currently the most under-served continent in terms of the information and communication technologies. Hence the collaboration amongst tertiary education institutes in Africa is imperative to make them key players in the enhancement of information and communication technologies for society (Ravinder 2008). GARNET like most other African NRENs has gone through several iterations of starting and stopping, various Boards and memberships, and various models of operations, which did not make any significant process in providing a sustainable NREN. Current attempts to have a sustainable NREN have been directed towards providing technical and services oriented solutions by focusing on the business model and financial plan(casefornren.org). Beyond merely the technical aspects of scalability, our concerns lie in how to reproduce and translate the necessary learning processes alongside the spreading of artifacts, funding, and people. (Braa, Monteiro et al 2004). A conscious effort has to be made using the theory of Information infrastructures to look at the collection of governance, policy, structures, people, procedures and technologies that Page | 46 ISSN 2223-7062 Proceedings and Report of the 9th UbuntuNet Alliance Annual Conference, 2016 pp 45-52 make up an NREN and its infrastructure in order to make it sustainable (Star and Ruhleder 1996). Without a conscious effort to achieve sustainable systems, initiatives from aid organisations, governments and NGOs are likely to replicate past outcomes of lengthy technology deployment and fast technology abandonment (Beardon et al. 2004). In order to leapfrog NRENs into becoming a vibrant and sustainable, the practices that have worked elsewhere on the continent should be reinforced. There is no need to rebuild the same problems in the new networks we are building. Instead there is a need to make the NREN stronger by building an organization with and active and vibrant community. In order to achieve this, interventions would have to be taken in the areas of governance, policies, procedures as well as the products and services that the NRENs of today would be providing to its community of users and practitioners like Universities ICT Directors, Researchers, Academicians, Librarians and other stakeholders. The presentation will propose key interventions that would be the set of actionable items for Governments, Donors agencies and other relevant stakeholders that are interested in either establishing or strengthen NRENs in Africa could use to ensure that they would be viable.
Keywords: NREN; Africa; National Research; Education Network